2009
DOI: 10.3921/joptom.2009.27
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Blepharoptosis and Eyelid Swelling Caused by Silicone Oil

Abstract: The purpose of this article is to report a case of upper eyelid mechanical ptosis caused by silicone oil migration in a Jordanian patient after pars plana vitrectomy and intraocular silicone oil injection. A 20-year-old male patient was referred to the oculoplastic clinic for the management of a left upper eyelid swelling and complete ptosis that developed 12 years after pars plana vitrectomy and silicone oil placement for retinal detachment secondary to perforating eye injury. Eye examination showed upper eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Dehiscence of the levator aponeurosis was not observed in the current case, but it was reported in previous case reports [ 14 ].…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Dehiscence of the levator aponeurosis was not observed in the current case, but it was reported in previous case reports [ 14 ].…”
Section: Discussionsupporting
confidence: 42%
“…Intraocular silicone oil is associated with a number of complications such as glaucoma, cataract, subretinal migration of silicone oil, and proliferation of epiretinal and subretinal fibrosis, keratopathy, and in rare situations the migration of silicone oil into the orbit. Migration of silicone oil into the orbit and upper eyelid was also reported after retina surgery following pars plana vitrectomy due to proliferative diabetic retinopathy [ 6 ], endogenous endophthalmitis [ 13 ] and penetrating eye trauma [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a few case reports of postoperative ptosis due to migration of silicone oil into the upper eyelid. [17][18][19][20][21][22][23] It usually occurs between 3 and 19 years after the procedure and is associated with eyelid inflammatory signs such as erythema and swelling which is not consistent with the series. [17][18][19][20][21][22][23] One of the reasons for postoperative ptosis after intraocular procedures has been myotoxic and neurotoxic effects of the local anesthesia.…”
Section: Discussionmentioning
confidence: 83%
“… 17 One of the complications of intraocular SO tamponade is its extraocular seepage. Studies have reported escape of SO and its migration into the eyelid with mechanical blepharoptosis, 18 cerebral migration, 19 migration in the SC space (through Molteno implant 5 or Ahmed glaucoma valve 20 ), and formation of SC cysts. 21 Hyung and Min reported dellen disappearance after removal of SCSO.…”
Section: Discussionmentioning
confidence: 99%